Precipitated silica with improved processing properties
By controlling the pH value and surface area of silica, the problem of insufficient dispersion ability in the elastomeric matrix is solved, and better enhancement effect and processing characteristics are achieved, which is suitable for applications such as tire tread.
Patent Information
- Application Number
- CN202510084181.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2018-11-29
- Filing Date
- 2019-07-12
- Publication Date
- 2025-04-22
AI Technical Summary
In the prior art, the dispersion ability of precipitated silica with high surface area in the elastomer matrix is insufficient, resulting in poor enhancement effects and processing characteristics.
Precipitated silica with improved dispersion ability was prepared by controlling the pH of silica within the acidic range (less than 5.5), combining high surface area and wide aggregate size distribution.
The dispersion ability of precipitated silica in the elastomeric matrix is improved, and the mechanical properties and processing characteristics of the polymer composition are enhanced, especially in tire tread applications, showing better wear resistance and energy dissipation characteristics.
Smart Images

Figure BDA0005249631850000151 
Figure BDA0005249631850000161 
Figure BDA0005249631850000221
Abstract
Description
This application is a divisional application of the following application: Application date: July 12, 2019; Application number: 2019800449064; Invention name: "Precipitated silica with improved processing characteristics". Technical Field
[0001] The present invention relates to precipitated silicas having improved dispersibility in elastomeric compositions. Background Art
[0002] The use of precipitated silica as a reinforcing filler in polymer compositions, in particular in elastomeric compositions, is known. Such use is very demanding: the filler should be easily and effectively incorporated and dispersed in the elastomeric matrix and typically form chemical bonds with one or more elastomers together with a coupling agent, thereby resulting in a high and uniform reinforcement of the elastomeric composition. Silica-filled elastomeric compositions can be used particularly advantageously in tire formulations. Tire treads filled with so-called highly dispersible silicas have made it possible to achieve a compromise in properties in terms of rolling resistance, wear resistance and grip that cannot be obtained with conventional tire carbon blacks.
[0003] Precipitated silicas with a high surface area are known. For example, WO 03 / 016215 A1 discloses precipitated silicas with a high surface area and a broad particle size distribution.
[0004] Silica with a broader particle size distribution allows obtaining elastomeric compositions with reduced energy dissipation properties (and therefore reduced heat build-up) and good levels of reinforcement when compared to precipitated silica with the same surface area.
[0005] The advantage of using high surface area silica lies mainly in the possibility of increasing the number of bonds of silica to the elastomer and thus increasing its reinforcement level. It would therefore appear advantageous to use silica having a high surface area in tire tread rubber compositions, which surface area can be greater than that conventionally used, especially for improving the wear resistance of the tire.
[0006] However, it has been observed that the ability of charges to disperse in an elastomeric matrix and the increase of its surface area are contradictory properties. In fact, a large surface area means increased interactions between charged objects and therefore poor dispersion and mixing in the elastomeric matrix.
[0007] Therefore, there is a constant need for novel precipitated silicas for use as reinforcing fillers in polymer compositions which provide an optimal balance between all the requirements mentioned above. Summary of the invention
[0008] It has been unexpectedly discovered that the ability of precipitated silicas having high surface area and large aggregate size distribution to disperse in an elastomeric matrix can be improved if the pH of the silica is acidic. In particular, it has been discovered that precipitated silicas having high surface area, large aggregate size distribution and a pH of less than 5.5 are more easily dispersed in an elastomeric matrix.
[0009] Therefore, a first object of the present invention is a precipitated silica, characterized in that: -More than 140m 2 CTAB surface area S / g CTAB ; - an aggregate size distribution width Ld of at least 1.2 measured by centrifugal sedimentation; - a pH of less than 5.5; and - Carbon content less than 1500 ppm.
[0010] In the remainder of this document, the terms "silica" and "precipitated silica" may be used interchangeably to refer to precipitated silica.
[0011] CTAB surface area S CTAB is a measure of the external specific surface area as determined by measuring the amount of N-hexadecyl-N,N,N-trimethylammonium bromide adsorbed on the silica surface at a given pH.
[0012] CTAB surface area S CTAB More than 150m 2 / g, preferably greater than 160m 2 / g. CTAB surface area S CTAB Typically greater than 170m 2 / g, preferably greater than 180m 2 / g. CTAB surface area S CTAB Even equal to or greater than 190m 2 / g, even greater than 200m 2 / g, even greater than 230m 2 / g.
[0013] CTAB surface area S CTAB No more than 400m 2 / g, typically 380m 2 / g. CTAB surface area S CTAB Can be lower than 350m 2 / g.
[0014] For elastomer reinforcement applications, the CTAB surface area S CTAB The favorable range is: 160m 2 / g to 400m 2 / g, 170m 2 / g to 400m 2 / g, 180m 2 / g to 350m 2 / g, preferably 190m 2 / g to 350m 2 / g, 200m 2 / g to 350m 2 / g, even 220m 2 / g to 350m 2 / g, preferably 180m 2 / g to 300m 2 / g, and 190m 2 / g to 300m 2 / g.
[0015] The precipitated silica of the present invention is further characterized by a broad aggregate size distribution. The term "aggregate" is used herein to refer to an aggregate of primary silica particles. An aggregate is the smallest collection of primary silica particles that can be broken up by mechanical action.
[0016] The parameter Ld, defined as Ld = (d84 - d16) / d50, is determined by centrifugal sedimentation in a disc centrifuge as described in detail below and is used to characterize the breadth of the aggregate size distribution. Ld is defined as follows: Ld=(d84-d16) / d50 Wherein dn is such diameter, and n% of total measured mass is found below this diameter. Ld is dimensionless (adimensional number). Aggregate size distribution width Ld is calculated on the cumulative aggregate size curve. As an example, d50 represents such diameter, and 50% of aggregate total mass is found below this diameter (and above). Therefore, d50 represents the median aggregate size of a given distribution, wherein the term "size" in this context should mean "diameter".
[0017] The particle size distribution width Ld is at least 1.2, typically at least 1.3. The particle size distribution width Ld is not greater than 4.0, typically not greater than 3.5.
[0018] Advantageously, the particle size distribution width Ld of the silica of the present invention is in the range of 1.2 to 3.5, even in the range of 1.3 to 3.2. The particle size distribution width Ld of the silica of the present invention may be in the range of 1.2 to 3.0, preferably in the range of 1.3 to 2.5.
[0019] The silica of the present invention does not comprise any organic moieties covalently attached to its surface.Preferably, the silica of the present invention does not comprise any organic moieties adsorbed or covalently attached to its surface.
[0020] The silicon dioxide of the present invention has a carbon content of less than 1500ppm, or even less than 1400ppm. Preferably, the silicon dioxide of the present invention has a carbon content of no more than 1000ppm. More preferably, the carbon content of the silicon dioxide of the present invention is less than 500ppm, more preferably less than 100ppm. The carbon content of the silicon dioxide of the present invention can even be less than 10ppm.
[0021] The pH of the silica of the present invention is less than 5.5, preferably less than 5.2, more preferably less than 5.0, and even less than 4.5. The pH is typically not less than 2.5, preferably not less than 3.0, usually not less than 3.5.
[0022] It has been found that precipitated silicas having a pH of less than 5.5 are more easily dispersed in an elastomeric matrix when compared to similar precipitated silicas having a higher pH.
[0023] In particular, it has been found that the precipitated silicas of the present invention are characterized by a high intrinsic ability to disperse in elastomeric compositions. This ability can be illustrated by the deagglomeration rate α (measured according to the Deagglomeration Test as described below). It has been found that the deagglomeration rate α of the silicas of the present invention is typically at least 15% higher than the deagglomeration rate α of a precipitated silica having the same surface area and aggregate size distribution breadth but at a higher pH.
[0024] The silicon dioxide of the present invention generally has a value equal to or greater than 0.5×10 -2 μm -1 min -1 The depolymerization rate α can be equal to or greater than 0.6×10 -2 μm -1 min -1 .
[0025] In a first advantageous embodiment, the silica of the invention is characterized in that: -More than 140m 2 / g, preferably greater than 160m 2 CTAB surface area S / g CTAB ; - an aggregate size distribution width Ld of at least 1.2 measured by centrifugal sedimentation; - pH less than 5.5; - A carbon content of less than 1500 ppm; and -Equal to or greater than 0.5×10 -2 μm -1 min -1 The depolymerization rate α.
[0026] In a further advantageous embodiment, the silicon dioxide of the invention is characterized in that: -More than 160m 2 CTAB surface area S / g CTAB ; - an aggregate size distribution width Ld of at least 1.2 measured by centrifugal sedimentation; - pH less than 5.5; - A carbon content not exceeding 1000 ppm; and -Equal to or greater than 0.5×10 -2 μm -1 min -1 The depolymerization rate α.
[0027] Typically, the precipitated silica of the present invention is characterized as follows according to the ratio V (d5-d50) / V (d5-d100) The large pore volume distribution is defined as (d5-d50) represents the pore volume formed by pores with diameters between d5 and d50 and V (d5-d100) represents the pore volume formed by pores with diameters between d5 and d100, where dn is the pore diameter for which n% of the total surface area of all pores is formed by pores with diameters larger than that diameter.
[0028] The silica of the present invention typically has a ratio V equal to or greater than 0.60, preferably equal to or greater than 0.65. (d5-d50) / V (d5-d100) Ratio V (d5-d50) / V (d5-d100) Typically no more than 1.20.
[0029] The precipitated silica according to the invention has a thickness of at least 150 m 2 / g, at least 165m 2 / g, especially at least 170m 2 / g and preferably at least 190m 2 BET surface S / g BET The BET surface can even be at least 200 m 2 / g. The BET surface is usually up to 450m 2 / g, especially up to 420m 2 / g, and even up to 400m 2 / g.
[0030] The silicon dioxide of the present invention is characterized by greater than 3.5 2 The number of silanols SiOH (N SiOH / nm2 ). per nm 2The silanol SiOH number is typically between 3.5 and 6.0, preferably between 3.5 and 5.5.
[0031] The silica of the invention may contain additional cations. Notable non-limiting examples of suitable cations are for example Al, Mg, Ca or Zn.
[0032] In one embodiment of the present invention, the precipitated silica contains more than 1500 ppm aluminum, typically more than 2000 ppm. The amount of aluminum is defined as the amount of aluminum metal weight relative to the weight of silica. The amount of aluminum typically does not exceed 10000 ppm.
[0033] In a second embodiment, the silica of the present invention contains no or low trace amounts of other cations, such as aluminum, which are typically contained in the silicate starting material of the precipitated silica. Among the additional elements, aluminum may be mentioned. In this second embodiment, the aluminum content in the silica of the present invention generally does not exceed 1400 ppm, preferably it does not exceed 1000 ppm and more preferably it does not exceed 500 ppm.
[0034] The second object of the present invention is a method for preparing the precipitated silica of the first object, the method comprising: (i) providing a starting solution having a pH of 2.0 to 5.0, (ii) adding silicate and acid to the starting solution simultaneously so that the pH of the reaction medium is maintained in the range of 2.0 to 5.0, (iii) stopping the addition of said acid and said silicate and adding a base to the reaction medium to raise the pH of said reaction medium to a value of 7.0 to 10.0, (iv) adding silicate and acid simultaneously to the reaction medium such that the pH of the reaction medium is maintained in the range of 7.0 to 10.0, (v) stopping the addition of the silicate while continuing to add the acid to the reaction medium to reach a pH of the reaction medium of less than 5.5 and obtaining a suspension of precipitated silica, and (vi) filtering the suspension of precipitated silica to provide a filter cake; (vii) subjecting the filter cake to a liquefaction step in the presence of an inorganic acid so that the pH of the resulting precipitated silica is less than 5.5 to obtain a suspension of precipitated silica; and (viii) optionally, drying the precipitated silica obtained after the liquefaction step.
[0035] The term "base" is used herein to refer to one or more than one base that can be added during the process of the method of the present invention, and includes the group consisting of silicates as defined below. Any base can be used in the method. Notable non-limiting examples of suitable bases are, for example, silicates, alkali metal hydroxides and ammonia. The base is preferably selected from alkali metal hydroxides, typically sodium hydroxide or potassium hydroxide, or ammonia.
[0036] The term "silicate" is used herein to refer to one or more than one silicate that may be added during the process of the method of the invention. The silicate is typically selected from the group consisting of alkali metal silicates. The silicate is advantageously selected from the group consisting of sodium silicate and potassium silicate. The silicate may be in any known form, such as a metasilicate or a disilicate.
[0037] In the case of sodium silicate, the latter generally has a SiO2 / Na2O weight ratio of from 2.0 to 4.0, in particular from 2.4 to 3.9, for example from 3.1 to 3.8.
[0038] The silicate may have a concentration (expressed as SiO2) of 3.9 wt% to 25.0 wt%, for example 5.6 wt% to 23.0 wt%, in particular 5.6 wt% to 20.7 wt%.
[0039] The term "acid" is used herein to refer to one or more than one acid that may be added during the process of the method of the invention. Any acid may be used in the method. Typically, inorganic acids such as sulfuric acid, nitric acid, phosphoric acid or hydrochloric acid, or organic acids such as carboxylic acids, for example acetic acid, formic acid or carbonic acid are used.
[0040] The acid can be metered into the reaction medium in dilute or concentrated form. The same acid can be used in different concentrations at different stages of the process. Preferably, the acid is sulfuric acid.
[0041] In a preferred embodiment of the method, sulfuric acid and sodium silicate are used in all stages of the method. Preferably, the same sodium silicate, i.e. sodium silicate with the same concentration expressed as SiO2, is used in all stages of the method.
[0042] In step (i) of the method, a starting solution having a pH of 2.0 to 5.0 is provided in a reaction vessel. The starting solution is an aqueous solution, and the term "aqueous" indicates that the solvent is water.
[0043] Preferably, the starting solution has a pH of 2.5 to 5.0, especially 2.8 to 4.4; for example, 3.0 to 4.0.
[0044] The starting solution may be obtained by adding an acid to water so as to obtain the pH value as detailed above.
[0045] Alternatively, the starting solution may contain a silicate. In this case, the starting solution may be obtained by adding an acid to a mixture of water and a silicate to obtain a pH of 2.0 to 5.0.
[0046] The starting solution of step (i) may or may not contain an electrolyte. Preferably, the starting solution of step (i) contains an electrolyte.
[0047] The term "electrolyte" is used herein in its generally recognized meaning, i.e. to designate any ionic or molecular substance that decomposes or dissociates to form ions or charged particles when in solution. The term "electrolyte" is used herein to indicate that one or more than one electrolyte may be present. Mention may be made of electrolytes such as salts of alkali metals and alkaline earth metals. Advantageously, the electrolyte used in the starting solution is a salt of the metal of the starting silicate and the acid used in the process. Notable examples are, for example, sodium chloride in the case of the reaction of sodium silicate with hydrochloric acid, or, preferably, sodium sulfate in the case of the reaction of sodium silicate with sulfuric acid. The electrolyte does not contain aluminum.
[0048] Preferably, when sodium sulfate is used as electrolyte in step (i), its concentration in the starting solution is 8 g / L to 40 g / L, especially 10 g / L to 35 g / L, for example 10 g / L to 30 g / L.
[0049] Step (ii) of the method comprises adding acid and silicate to the starting solution simultaneously. The rate of addition of acid and silicate during step (ii) is controlled in such a way that the pH of the reaction medium is maintained in the range of 2.0 to 5.0. The pH of the reaction medium is preferably maintained in the range of 2.5 to 5.0, in particular in the range of 2.8 to 5.0, for example in the range of 2.8 to 4.5.
[0050] The simultaneous addition in step (ii) is advantageously carried out in such a way that the pH of the reaction medium is always equal (within ±0.2 pH units) to the pH reached at the end of step (i).
[0051] Preferably, step (ii) consists of the simultaneous addition of acid and silicate as detailed above.
[0052] In one embodiment of the process of the present invention, an intermediate step (ii') may be performed between step (i) and step (ii), wherein silicate and acid are added to the starting solution such that the pH of the reaction medium is maintained in the range of 2.0 to 9.5. For all or only part of step (ii'), the addition of silicate and acid may be simultaneous. Step (ii') typically lasts 1 to 10 minutes, preferably 2 to 8 minutes, before step (ii) begins.
[0053] Next, in step (iii), the addition of acid and silicate is stopped and a base is added to the reaction medium. When the pH of the reaction medium reaches a value of 7.0 to 10.0, preferably 7.5 to 9.5, the addition of the base is stopped.
[0054] In a first embodiment of the process, the base is a silicate.Thus, in step (iii), the addition of the acid is stopped while the addition of silicate to the reaction medium continues until a pH of 7.0 to 10.0, preferably 7.5 to 9.5 is reached.
[0055] In a second embodiment of the process, the base is different from the silicate and is selected from the group consisting of alkali metal hydroxides, preferably sodium hydroxide or potassium hydroxide. When sodium silicate is used in the process, the preferred base may be sodium hydroxide.
[0056] Thus, in this second embodiment of the process, in step (iii), the addition of acid and silicate is stopped and a base other than silicate is added to the reaction medium until a pH of 7.0 to 10.0, preferably 7.5 to 9.5 is reached.
[0057] At the end of step (iii), i.e. after the addition of the alkali has been stopped, it may be advantageous to carry out a maturing step of the reaction medium. This step is preferably carried out at the pH obtained at the end of step (iii). The maturing step may be carried out while stirring the reaction medium. The maturing step is preferably carried out under stirring of the reaction medium within a time period of 2 to 45 minutes, in particular 5 to 25 minutes. Preferably, the maturing step does not include any addition of an acid or a silicate.
[0058] After step (iii) and the optional maturation step, simultaneous addition of acid and silicate is carried out such that the pH of the reaction medium is maintained in the range from 7.0 to 10.0, preferably in the range from 7.5 to 9.5.
[0059] The simultaneous addition of acid and silicate (step (iv)) is typically carried out in such a way that the pH of the reaction medium is maintained equal to the pH reached at the end of the preceding step, step (iii) (within ± 0.2 pH units).
[0060] It should be noted that the process of the present invention may include additional steps. For example, between step (iii) and step (iv), and in particular between the optional aging step after step (iii) and step (iv), an acid may be added to the reaction medium. The pH of the reaction medium after the addition of this acid should be maintained in the range of 7.0 to 9.5, preferably in the range of 7.5 to 9.5.
[0061] In step (v), the addition of silicate is stopped while continuing to add acid to the reaction medium so as to obtain a pH value in the reaction medium of less than 5.5, preferably from 3.0 to 5.5, especially from 3.0 to 5.0. A suspension of precipitated silica is obtained in the reaction vessel.
[0062] At the end of step (v), and therefore after the addition of acid to the reaction medium has been stopped, a maturation step may advantageously be carried out. This maturation step may be carried out at the same pH obtained at the end of step (v) and under the same time conditions as those described above for the maturation step that may optionally be carried out between steps (iii) and (iv) of the process.
[0063] The reaction vessel in which the entire reaction of the silicate with the acid takes place is usually equipped with appropriate stirring and heating equipment.
[0064] The entire reaction of silicate with acid (steps (i) to (v)) is generally carried out at a temperature of 40 to 97°C, especially 60 to 96°C, preferably 80 to 956°C, more preferably 85 to 95°C.
[0065] According to one variant of the invention, the entire reaction of the silicate with the acid is carried out at a constant temperature generally ranging from 40°C to 97°C, in particular from 80°C to 956°C and even from 85°C to 95°C.
[0066] According to another variant of the invention, the temperature at the end of the reaction is higher than the temperature at the beginning of the reaction: thus, the temperature at the beginning of the reaction (for example during steps (i) to (iii)) is preferably kept in the range of 40°C to 92°C, and the temperature is then increased, preferably to a value in the range of 80°C to 96°C, or even 85°C to 95°C, and the temperature is kept at this value (for example during steps (iv) and (v)) until the end of the reaction.
[0067] At the end of the steps just described, a suspension of precipitated silica is obtained which is subsequently separated (liquid / solid separation). The process typically comprises a further step (vi) of filtering the suspension and drying the precipitated silica.
[0068] The separation carried out in the preparation process according to the invention generally comprises filtration, followed by washing, if necessary. The filtration is carried out according to any suitable method, for example by a belt filter, a rotary filter, such as a vacuum filter, or, preferably, a filter press.
[0069] The filter cake is then subjected to a liquefaction operation, during which a mineral acid is added to the filter cake. The acid is selected from the group consisting of sulfuric acid, hydrochloric acid, phosphoric acid, nitric acid. The acid is preferably sulfuric acid or phosphoric acid. The amount of mineral acid added to the filter cake during the liquefaction step is such that the pH of the resulting precipitated silica is less than 5.5, preferably less than 4.5. The pH may even be less than 3.5, although it is usually not less than 3.0.
[0070] The term "liquefaction" is intended here to indicate a process in which a solid, ie a filter cake, is transformed into a fluid-like substance. After the liquefaction step, the filter cake is in a flowable, fluid-like form and the precipitated silica is in the form of a suspension.
[0071] The liquefaction step may include a mechanical treatment which results in a reduction in the granulometry of the silica in the suspension. The mechanical treatment may be performed by passing the filter cake through a high shear mixer, a colloid-type mill or a ball mill.
[0072] During the liquefaction step, an aluminum compound may be added to the filter cake, provided that the pH of the resulting precipitated silica is less than 5.5, preferably less than 5.0.
[0073] The suspension of precipitated silicon dioxide obtained after the liquefaction step is preferably subsequently dried.
[0074] Drying can be carried out according to means known in the art. Preferably, drying is carried out by atomization. For this reason, any type of suitable atomizer can be used, in particular turbine, nozzle, hydraulic or two-fluid spray dryers. In general, when using a filter press to filter, a nozzle spray dryer is used, and when using a vacuum filter to filter, a turbo spray dryer is used.
[0075] When a nozzle spray dryer is used for the drying operation, the precipitated silica that can then be obtained is generally in the form of substantially spherical beads. After this drying operation, optionally, a grinding or micronizing step can be carried out on the recovered product; the precipitated silica that can then be obtained is generally in the form of a powder.
[0076] When a turbo spray dryer is used for the drying operation, the precipitated silica that can then be obtained can be in the form of a powder.
[0077] Finally, the dried, ground or micronized product as previously indicated may optionally be subjected to an agglomeration step comprising, for example, direct compression, wet granulation (ie with a binder such as water, silica suspension, etc.), extrusion or, preferably, dry pressing.
[0078] The precipitated silica that can then be obtained by this agglomeration step is generally in the form of granules.
[0079] The precipitated silica according to the invention or obtained by the above-described process according to the invention can be used in a variety of applications.
[0080] For example, the precipitated silica of the present invention can be used as a catalyst support. It can be used as an absorbent for active materials, such as liquids, especially for use in foods, such as vitamins (vitamin E) or choline chloride. It can be used as a tackifier, texturizer or anti-caking agent, as a battery separator component, or as an additive for toothpaste, concrete, or paper.
[0081] However, the precipitated silicas of the invention can be used particularly advantageously for the reinforcement of natural or synthetic polymers.
[0082] Elastomer compositions containing the silica of the present invention are found to have improved mechanical and reinforcing properties relative to compositions comprising precipitated silica at a pH above 5.5. The improved dispersibility even at the high surface area of the silica of the present invention provides polymer compositions with better energy dissipation properties and even improved wear resistance.
[0083] The use of the silica of the present invention also provides improved processing characteristics of the elastomeric composition, especially when a high surface area silica is used, such as a CTAB surface area greater than 190 m 2 / g, typically even greater than 210m 2 / g of precipitated silica.
[0084] Therefore, another object of the present invention is a composition comprising a silica according to the invention as defined above and at least one polymer.When referring to the polymers in the composition, the phrase "at least one" is used herein to indicate that one or more than one polymer of each type may be present in the composition.
[0085] The expression "copolymer" is used herein to refer to a polymer comprising recurring units derived from at least two monomer units having different natures.
[0086] At least one polymer may be selected from a thermosetting polymer and a thermoplastic polymer. Notable non-limiting examples of thermosetting polymers include thermosetting resins such as epoxy resins, unsaturated polyester resins, vinyl ester resins, phenolic resins, epoxy acrylate resins, urethane acrylate resins, phenoxy resins, alkyd resins, urethane resins, maleimide resins, and cyanate resins.
[0087] Notable non-limiting examples of suitable thermoplastic polymers include styrene-based polymers such as polystyrene, (meth)acrylate / styrene copolymers, acrylonitrile / styrene copolymers, styrene / maleic anhydride copolymers, ABS; acrylic polymers such as polymethyl methacrylate; polycarbonates; polyamides; polyesters such as polyethylene terephthalate and polybutylene terephthalate; polyphenylene ether; polysulfones; polyaryletherketones; polyphenylene sulfide; thermoplastic polyurethanes; polyolefins such as polyethylene, polypropylene, polybutylene, poly-4-methylpentene, ethylene / propylene copolymers, ethylene / α-olefin copolymers; copolymers of α-olefins and various monomers such as ethylene / vinyl acetate copolymers, ethylene / (meth)acrylate copolymers, ethylene / maleic anhydride copolymers, ethylene / acrylic acid copolymers; aliphatic polyesters such as polylactic acid, polycaprolactone, and aliphatic diol / aliphatic dicarboxylic acid copolymers.
[0088] The silica of the invention can advantageously be used as a reinforcing filler in elastomeric compositions. A preferred object of the present invention is therefore a composition comprising the silica of the invention and one or more elastomers, preferably exhibiting at least one glass transition temperature between -150°C and +300°C, for example between -150°C and +20°C.
[0089] The notable non-limiting example of suitable elastomer is diene elastomer.For example, an elastomer derived from aliphatic or aromatic monomers can be used, which comprises at least one degree of unsaturation, such as, especially, ethylene, propylene, butadiene, isoprene, styrene, acrylonitrile, isobutylene or vinyl acetate, polybutyl acrylate or their mixture.It can also be mentioned that functionalized elastomers are elastomers and halogenated polymers functionalized by chemical groups (for example, by functional groups that can react with silicon dioxide surfaces) positioned along the macromolecular chain and / or at one or more of its ends.It can be mentioned that polyamides, ethylene homopolymers and copolymers, propylene homopolymers and copolymers.
[0090] Among the diene elastomers, mention may be made, for example, of polybutadiene (BR), polyisoprene (IR), butadiene copolymers, isoprene copolymers, or mixtures thereof, and in particular styrene / butadiene copolymers (SBR, in particular ESBR (emulsion) or SSBR (solution)), isoprene / butadiene copolymers (BIR), isoprene / styrene copolymers (SIR), isoprene / butadiene / styrene copolymers (SBIR), ethylene / propylene / diene terpolymers (EPDM), and also related functionalized polymers (for example having pendant polar groups or polar groups at the chain ends which are capable of interacting with silica).
[0091] Mention may also be made of natural rubber (NR) and epoxidized natural rubber (ENR).
[0092] The polymer composition may be vulcanized with sulfur, or crosslinked, in particular with peroxides or other crosslinking systems (eg diamines or phenolic resins).
[0093] In general, the polymer compositions additionally comprise at least one coupling agent and / or at least one covering agent; they may also comprise, in particular, antioxidants.
[0094] As non-limiting examples, "symmetrical" or "asymmetrical" silane polysulfides may be used in particular as coupling agents; mention may be made more particularly of: bis((C1-C4)alkoxy(C1-C4)alkylsilyl(C1-C4)alkyl)polysulfides (in particular disulfides, trisulfides or tetrasulfides), such as, for example, bis(3-(trimethoxysilyl)propyl)polysulfide or bis(3-(triethoxysilyl)propyl)polysulfide, such as triethoxysilylpropyltetrasulfide. Mention may also be made of monoethoxydimethylsilylpropyltetrasulfide. Mention may also be made of silanes containing masked or free thiol functions.
[0095] The coupling agent may be pre-grafted onto the polymer. It may also be used in the free state or grafted onto the surface of the silica. The coupling agent may optionally be combined with a suitable "coupling activator", i.e. a compound which, when mixed with the coupling agent, increases the effectiveness of the latter.
[0096] The weight ratio of the silica of the present invention in the polymer composition can vary within a fairly wide range. It usually accounts for 10% to 200% by weight, especially 20% to 150% by weight, in particular 20% to 80% by weight, for example 30% to 70% by weight. Alternatively, the weight ratio of the silica of the present invention in the polymer composition can be 80% to 120% by weight, for example 90% to 110% by weight of the amount of one or more polymers.
[0097] The silica according to the invention may advantageously constitute the entirety of the reinforcing inorganic filler and even the entirety of the reinforcing filler of the polymer composition.
[0098] The silica according to the invention may optionally be combined with at least one other reinforcing filler, such as, in particular, a commercial highly dispersible silica, such as, for example 1165MP, 1115MP or 1085MP (commercially available from Solvay); another reinforcing inorganic filler such as, for example, alumina, indeed even a reinforcing organic filler, especially carbon black (optionally covered with an inorganic layer such as silica). The silica according to the invention then preferably constitutes at least 50% by weight, indeed even at least 80% by weight, of the total amount of reinforcing filler.
[0099] Compositions comprising the precipitated silica of the present invention can be used to manufacture a number of articles. Non-limiting examples of articles comprising the silica of the present invention or the above-mentioned polymer composition are, for example, soles, floor coverings, gas barriers, flame retardant materials and also engineering parts, such as rollers for ropeways, seals for household appliances, seals for liquid or gas pipelines, brake system seals, pipes, sheaths (especially cable sheaths), cables, engine mounts, battery separators, conveyor belts, transmission belts or dampers. Advantageously, the silica of the present invention can be used to manufacture tires, especially tire treads, especially tire treads for light vehicles or heavy vehicles.
[0100] Should the disclosure of any patents, patent applications, and publications incorporated by reference into this application conflict with the description of the present application to the extent that it renders a term unclear, the present description shall take precedence.
[0101] The present invention will now be described in more detail with reference to the following examples, the purpose of which is merely illustrative and not limiting the scope of the present invention.
[0102] Analytical methods
[0103] The physicochemical properties of the precipitated silicas of the present invention were determined using the methods described below.
[0104] Determination of CTAB surface area
[0105] The CTAB surface area (S) was determined according to an internal method derived from standard NF ISO 5794-1, annex G. CTAB )value.
[0106] Determination of BET surface area
[0107] The BET surface area S is determined according to the Brunauer-Emmett-Teller method as detailed in standard NF ISO 5794-1, Annex E (June 2010) BET , with the following adjustments: the sample is pre-dried at 200°C ± 10°C; the partial pressure P / P used for measurement 0 Between 0.05 and 0.3.
[0108] Determination of particle size distribution and particle size by centrifugal sedimentation in a disc centrifuge (CPS)
[0109] The values of d50, d16, d84 and Ld are determined by centrifugal sedimentation in a disc centrifuge using a centrifugal optical sedimentation instrument model "CPSDC 24000UHR" sold by CPS Instruments. The instrument is equipped with the operating software supplied with the device (operating software version 11g).
[0110] Instruments used: For the measurement needs, the following materials and products were used: Ultrasonic system: 1500W generator model Sonics Vibracell VC1500 / VCX1500 equipped with 19mm probe (Converter: CV154 + Booster (Part No.: BHNVC21) + 19mm probe (Part No.: 630-0208)).
[0111] Analytical balance with an accuracy of 0.1 mg (e.g. Mettler AE260); Syringes: 1.0 ml and 2.0 ml with 20 ga needles; 50 mL highly shaped glass beaker (SCHOTT DURAN: 38 mm diameter, 78 mm height); magnetic stirrer with 2 cm stirring bar; container for ice bath during sonication.
[0112] Chemicals: deionized water; ethanol 96%; sucrose 99%; dodecane, all from Merck; PVC reference standard from CPS Instrument Inc.; The peak maximum of the reference standard used should be between 200 and 600 nm (eg 237 nm).
[0113] Preparation of the disc centrifuge
[0114] For the measurements, the following parameters were established: For the calibration standard parameters, the information of the PVC reference transmitted by the supplier was used. × cps = centipoise
[0115] System Configuration
[0116] The measurement wavelength was set to 405 nm. The following run time option parameters were established: Force Baseline: yes Correction for Non-Stokes: no Additional software noise filtering: no Baseline drift display: Show Calibration method: external Each calibration sample: 1
[0117] All other software options remain as set by the instrument manufacturer.
[0118] Preparation of the disc centrifuge
[0119] The centrifuge disk was rotated at 24000 rpm during 30 min. A density gradient of sucrose (CAS n° 57-50-1) was prepared as follows:
[0120] In a 50 mL beaker, prepare a 24 wt % aqueous solution of sucrose. In a 50 mL beaker, prepare an 8 wt % aqueous solution of sucrose. Once both solutions are homogenized individually, use a 2 mL syringe to take a sample from each solution and inject it into the spinning disk in the following order: Sample 1: 1.8 mL of 24 wt% solution Sample 2: 1.6 mL of 24 wt% solution + 0.2 mL of 8 wt% solution Sample 3: 1.4 mL of 24 wt% solution + 0.4 mL of 8 wt% solution Sample 4: 1.2 mL of 24 wt% solution + 0.6 mL of 8 wt% solution Sample 5: 1.0 mL of 24 wt% solution + 0.8 mL of 8 wt% solution Sample 6: 0.8 mL of 24 wt% solution + 1.0 mL of 8 wt% solution Sample 7: 0.6 mL of 24 wt% solution + 1.2 mL of 8 wt% solution Sample 8: 0.4 mL of 24 wt% solution + 1.4 mL of 8 wt% solution Sample 9: 0.2 mL of 24 wt% solution + 1.6 mL of 8 wt% solution Sample 10: 1.8 mL of 8 wt% solution
[0121] Prior to each injection into the dish, both solutions were homogenized in the syringe by aspirating approximately 0.2 mL of air followed by brief manual agitation for a few seconds to ensure that no liquid was lost.
[0122] These injections, with a total volume of 18 mL, were used to generate a density gradient that can be used to eliminate certain instabilities that may occur during the injection of the sample to be measured. To protect the density gradient from evaporation, we added 1 mL of dodecane in the rotating disk using a 2 mL syringe. The disk was then kept spinning at 24000 rpm for 60 min before any first measurement.
[0123] Sample preparation
[0124] 3.2g silica is weighed into a 50mL highly molded glass beaker (SCHOTT DURAN: 38mm in diameter, 78mm in height) and 40mL of deionized water is added to obtain an 8wt% silica suspension. The suspension is stirred with a magnetic stirrer (minimum 20s), and the beaker is then placed in a crystallization dish filled with ice and cold water. Take out the magnetic stirrer and place the crystallization dish under an ultrasonic probe, which is placed 1cm from the bottom of the beaker. The ultrasonic probe is set to 56% of its maximum amplitude and runs for 8 minutes. At the end of the ultrasonic treatment, the beaker is again placed on a magnetic stirrer stirred at a minimum of 500rpm using a 2cm magnetic stirring bar until after sampling.
[0125] The ultrasonic probe should be in proper working condition. The following checks should be performed and if negative results are obtained, a new probe should be used: Visual inspection of the physical integrity of the probe tip (roughness depth less than 2 mm measured with a precision caliper); Commercial silica The measured d50 of 1165MP should be 93nm±3nm.
[0126] analyze
[0127] Prior to analyzing each sample, the calibration standards were recorded. In each case, 0.1 mL of a PVC standard provided by CPS Instruments and whose characteristics were previously entered into the software was injected. It is important that the measurement is started in the software simultaneously with this first injection of the PVC standard. By ensuring that the measurement is started simultaneously with the injection, confirmation of the device should have been received prior to the injection of 100 μL of the pre-sonicated sample.
[0128] These injections were done using 2 clean 1 mL syringes.
[0129] At the end of the measurement, which reaches the end point of the time required to settle all particles of smaller diameter (configured in the software to 0.02 μm), the ratio of each diameter category is obtained. The curve obtained is called the aggregate size distribution.
[0130] Results: The values d50, d16, d84 and Ld are based on a distribution plotted on a linear scale. Integration of the particle size distribution function of the diameter allows obtaining the "cumulative" distribution, that is to say the total mass of particles between the smallest diameter and the diameter of interest. d50: is the diameter below and above which 50 mass % of the population is found. d50 is known as the median particle size, ie, the diameter, of silica aggregates. d84: is the diameter below which 84% of the total mass of the aggregate is measured. d16: is the diameter below which 16% of the total mass of the aggregate is measured. Ld: calculated according to the following formula: Ld = (d84-d16) / d50
[0131] Determination of pore volume and pore size by mercury porosimetry
[0132] Pore volume and pore size distribution using Micromeritics IV 9520 porosimeter; they are calculated by the Washburn relation using a contact angle θ equal to 140° and a surface tension γ equal to 485 dynes / cm. Each sample is dried in an oven at 200° C. at atmospheric pressure for 2 hours before the measurement. The starting weight of the silica placed in the model 10 penetrometer (accuracy 0.001 g) is chosen for good reproducibility of the measurements in such a way that the “stem volume used”, i.e. the percentage mercury (Hg) volume consumed to fill the penetrometer, is between 40% and 80%. The penetrometer is then slowly evacuated to 50 μm of Hg and kept at this pressure for 5 min.
[0133] Operates with software version IV 1.09 The device was used. No correction was made to the raw data. The measurement range was from 3.59 kPa (0.52 psi) to 413685 kPa (60000 psi), and at least 100 measurement points were used (19 measurement points from 3.59 kPa (0.52 psi) to 193 kPa (28 psi), with a 10 second equilibrium time, and then 81 points from 1.93 kPa (0.28 psi) to 413685 kPa (60000 psi), with a 20 second equilibrium time). Where appropriate, the software introduced additional measurement points if the mercury injection volume increment was >0.5 mL / g. The mercury injection curve was smoothed by means of the "smooth differential" function of the device software.
[0134] The Log Differential Intrusion (mL / g) versus pore size data was analyzed in the pore diameter range of 3.5 nm to 5 μm.
[0135] The pore volumes and pore diameters / radii given were measured by mercury (Hg) porosimetry using a Micromeritics Autopore IV 9520 porosimeter and calculated by the Washburn relationship with a contact angle θ equal to 140° and a surface tension γ equal to 485 dynes / cm; each sample was prepared as follows: each sample was previously dried in an oven at 200°C for 2 hours.
[0136] pH determination
[0137] The pH is measured according to the following method derived from standard ISO 787 / 9 (pH of a 5% suspension in water):
[0138] Equipment: Calibrated pH meter (reading accuracy 1 / 100), combination glass electrode, 200 mL beaker, 100 mL graduated cylinder, balance accurate to within approximately 0.01 g.
[0139] Procedure: 5.00 grams of silica were weighed (to within about 0.01 grams) into a 200 mL beaker. 95 mL of water measured from a graduated cylinder were then added to the silica powder. The suspension thus obtained was vigorously stirred (magnetic stirring) for 10 minutes. The pH measurement was then performed.
[0140] Depolymerization test (depolymerization rate α)
[0141] The deagglomeration rate, denoted as α, is measured by an ultrasonic disintegration test at 55% amplitude of a 750 watt probe operated in continuous mode (equivalent to a power delivered to the system of 90 + / - 5 W) (adjustment of the probe is performed with a reference silica sample). To prevent excessive heating of the ultrasonic probe during the measurement, the transducer of the ultrasonic probe is cooled with a stream of compressed air and the sonicated suspension is placed in an ice bath. This test allows continuous measurement of the change in the volume average size of the particle aggregates during sonication.
[0142] The apparatus used consists of a laser particle size analyzer (MASTERSIZER 3000 model sold by Malvern Instruments: He-Ne laser source emitting red light at a wavelength of 632.8 nm and blue light at a wavelength of 470 nm) and its preparation station (Malvern Hydro MV unit), between which is inserted a continuous flux flow treatment cell (10-50 mL reaction vessel from Sonics Materials) equipped with an ultrasonic probe (LAB 750-model 13 mm sonicator sold by SynapTec 750 Watts). A small amount (100 mg) of the silica to be analyzed is introduced into the preparation station together with 160 mL of water, the circulation rate being set to its maximum value (i.e. 3500 rpm). At least three consecutive measurements are carried out in order to determine the initial volume mean diameter of the aggregates, denoted d, using the Mie calculation method (refractive index of 1.44 and absorption index of 0.01; Malvern V3.50 software). V [0] Ultrasonic treatment (continuous mode) was then applied at 55% power (i.e. 55% of the maximum position of the tip amplitude or 90 + / - 5 W of power delivered to the system) and the volume mean diameter d V [t] was monitored over time t for approximately 8 minutes, with measurements taken approximately every 12 seconds. After the induction period (approximately 3-4 minutes), the inverse of the volume mean diameter 1 / d was observed V [t] varies linearly or substantially linearly with time t (disintegration steady state). The disintegration rate α changes from 1 / d to V [t] is calculated by linear regression of the curve of change with time t; it is expressed in μm -1 .min -1 express.
[0143] WO 99 / 28376 describes in detail a measuring device which can be used to carry out this ultrasonic disintegration test.
[0144] Determination of carbon content
[0145] Carbon content uses carbon / sulfur analyzer such as Horiba EMIA320V2 to measure.The principle of this carbon / sulfur analyzer is based on the combustion of solid sample in the oxygen stream in induction furnace (being adjusted to about 170mA) and in the presence of combustion promoter (about 2 grams of tungsten (particularly Lecocel 763-266) and about 1 gram of iron).The carbon (weight is about 0.2 gram) present in the sample to be analyzed is combined with oxygen to form CO , CO.These gases are analyzed by infrared detectors subsequently.The water produced during these oxidation reactions from the moisture of this sample and is removed by passing through the sleeve (cartridge) comprising dehydrating agent (magnesium perchlorate) so as not to interfere with infrared measurement.The result is expressed as the weight of element carbon in ppm.
[0146] Determination of aluminum content
[0147] The amount of aluminum was measured using XRF wavelength dispersive X-ray fluorescence spectrometry (using a WDXRF Panalytical instrument). The ion exchange reaction was performed in a 4 cm diameter cell under helium using a 200 μm ion exchange reaction mixture covered with a thin Prolene film (4 μm ) in a cell with silica powder in the range of 0.1% to 3.0% Al / SiO2.
[0148] The Al and Si fluorescence were measured using the following parameters: Al Kα angle 2θ = 144,9468° (20 s), background signal angle 2θ = -1,2030° (4 s), Si Kα angle 2θ = 109,1152° (10 s), tube power 4 kW (32 kV, 125 mA), PE002 crystal and 550 μm collimator, gas flux detector.
[0149] After digestion of the sample in hydrofluoric acid (e.g. 0.2 g-0.3 g SiO2 with 1 mL 40% fluorinated acid), the aluminum content in samples containing more than 3.0% Al / SiO2 is determined by ICP OES (Inductively Coupled Plasma Optical Emission Spectrometry). The transparent solution is diluted in a 5% aqueous nitric acid solution according to the expected Al concentration. The intensity measured at the Al specific wavelength (396.152 nm) is compared with a calibration curve in the range of 0.05 mg / L to 2.00 mg / L obtained under similar analytical conditions using aluminum standards (4 standards at 0.10 mg / L, 0.20 mg / L, 1.00 mg / L and 2.00 mg / L). The amount in the solid is obtained by calculation using the dilution factor and the dry extract of the measured silica.
[0150] per nm 2 Determination of the number of thiols
[0151] The amount of methanol grafted onto the silica surface was determined by2 The number of thiols on the surface area is determined. First, 1 gram of silica is suspended in 10 mL of methanol in a stirred autoclave. The sealed and insulated autoclave is heated to 200°C (40 bar) for 4 hours. The autoclave is then cooled in a cold water bath. The grafted silica is recovered by precipitation and the residual methanol is evaporated in a nitrogen stream. The grafted silica is vacuum dried at 130°C for 12 hours. The carbon content is determined by elemental analysis. 2 The thiol number is calculated using the following formula: N SiOH / nm2 =[(%Cg - %Cr) × 6.023 × 10 23 ] / [S BET ×10 18 ×12×100] Where %Cg: mass percentage of carbon present on the grafted silica; %Cr: mass percentage of carbon present on the original silica.
[0152] Examples
[0153] Example 1
[0154] 960 liters of water were introduced into a 2500 liter reactor and heated to 90° C. 15 kg of solid sodium sulfate were introduced into the reactor under stirring. Sulfuric acid (concentration: 96 wt %) was then added until a pH of 3.8 was reached.
[0155] Sodium silicate solution (SiO / Na O weight ratio equals 3.41 and density equals 1.231 kg / L) was introduced into the reactor simultaneously with sulfuric acid (concentration: 7.7 wt %) at a flow rate of 370 L / h over a period of 25 minutes. The flow rate was adjusted so that the pH of the reaction medium was maintained at a value of 3.9.
[0156] After 25 minutes of simultaneous addition at 90° C., the introduction of acid was stopped and the pH of the reaction medium was brought to 8.0. At the same time, the temperature was raised to 94° C. A further simultaneous addition was then carried out over a period of 18 minutes at a sodium silicate flow rate of 600 L / h (the same as for the first simultaneous addition of sodium silicate) and at an adjusted flow rate of sulfuric acid (concentration: 7.7 wt %), in order to maintain the pH of the reaction medium at a value of 8.0.
[0157] After this simultaneous addition, the reaction medium was brought to a pH of 4.5 by introducing sulfuric acid (concentration: 7.7 wt %). 2070 liters of precipitated silica suspension were obtained after this operation.
[0158] The suspension was filtered on a filter press and washed to give a precipitated silica cake having a solids content of 19.2% by weight.
[0159] Example 2
[0160] A portion of the silica cake obtained in Example 1 was then subjected to a liquefaction step by adding 1709 g of sulfuric acid solution (concentration: 7.7 wt %) to the cake in a reactor with continuous and vigorous stirring.
[0161] The liquefied cake was then spray dried using a nozzle atomizer to provide silica S 1. The properties of silica S 1 are reported below.
[0162] Comparative Example 1
[0163] The second part of the silica cake obtained in Example 1 was subjected to a liquefaction step by simultaneously adding sulfuric acid (concentration: 7.7 wt %) and sodium aluminate solution (Al / SiO2 ratio: 0.30 wt %) to the cake in a reactor with continuous vigorous stirring.
[0164] The liquefied cake was then spray dried using a nozzle atomizer to provide silica CS 1. The properties of silica CS 1 are reported below.
[0165] The depolymerization rate α of silica S1 according to the present invention is 40% higher than that of CS1, which indicates that silica S1 has better depolymerization ability.
[0166] Example 3
[0167] 1117 liters of water were introduced into a 2500 liter reactor and heated to 92° C. 17.9 kg of solid sodium sulfate were introduced into the reactor under stirring. Sulfuric acid (concentration: 96 wt %) was then added until the pH of the mixture reached 4.1.
[0168] Sodium silicate solution (SiO / Na O weight ratio equals 3.44 and density equals 1.231 kg / L) was introduced into the reactor simultaneously with sulfuric acid (concentration: 7.7 wt %) at a flow rate of 432 L / h over a period of 25 minutes. The flow rate was adjusted so that the pH of the reaction medium was maintained at a value of 4.2.
[0169] After 25 minutes of simultaneous addition at 92° C., the introduction of acid was stopped and the pH was brought to a value of 8.0 by continuing to add sodium silicate. At the same time, the temperature was raised to 96° C. Further simultaneous additions were then carried out over a period of 18 minutes at a flow rate of 709 L / h of sodium silicate and a flow rate of adjusted sulfuric acid (concentration: 96 wt %) in order to maintain the pH of the reaction medium at a value of 8.0.
[0170] After this simultaneous addition, the reaction medium was brought to a pH of 4.5 by introducing sulfuric acid (concentration: 96 wt %). 2060 liters of precipitated silica suspension were obtained after this operation.
[0171] The precipitated silica suspension was filtered on a filter press and washed to give a precipitated silica cake having a solids content of 22.5% by weight.
[0172] The obtained silica cake was subjected to a liquefaction step by adding 1452 g of sulfuric acid solution (concentration: 7.7 wt %) to the cake in a reactor with continuous and vigorous stirring.
[0173] This liquefied cake was then spray dried using a nozzle atomizer to provide silica S2. The properties of silica S2 are reported below.
[0174] Comparative Example 2
[0175] 1112 liters of water were introduced into a 2500 liter reactor and heated to 92° C. 17.9 kg of solid sodium sulfate were introduced into the reactor with stirring. Sulfuric acid with a concentration of 96% by weight was then added until a pH of 4.1 was reached.
[0176] Sodium silicate solution (wherein SiO / Na O weight ratio equals 3.44 and density equals 1.231 kg / L) is introduced into the reactor simultaneously with sulfuric acid (concentration: 7.7 wt %) at a flow rate of 432 L / h over a period of 25 minutes. The flow rate is adjusted so that the pH of the reaction medium is maintained at a value of 4.2.
[0177] After 25 minutes of simultaneous addition at 92° C., the introduction of acid was stopped and the pH was brought to a value of 8.0 by adding sodium silicate. At the same time, the temperature was raised to 96° C. Further simultaneous additions were then carried out over a period of 18 minutes at a flow rate of 709 L / h of sodium silicate and a flow rate of adjusted sulfuric acid (concentration: 96 wt %) in order to maintain the pH of the reaction medium at a value of 8.0.
[0178] After this simultaneous addition, the reaction medium was brought to a pH of 4.4 by introducing sulfuric acid (concentration: 96 wt %). 2060 liters of precipitated silica suspension were obtained after this operation.
[0179] The precipitated silica suspension was filtered on a filter press and washed to give a precipitated silica cake having a solids content of 22.0% by weight.
[0180] Then, in a reactor with continuous and vigorous stirring, 3748 g of sulfuric acid solution (concentration: 7.7 wt %) and 2021 g of sodium aluminate solution (Al 2 O 3 content: 22.5 wt %) were added to the cake to carry out a liquefaction step on the obtained silica cake.
[0181] This liquefied cake was then spray dried using a nozzle atomizer to provide silica CS2. The properties of silica CS2 are reported below.
[0182] The depolymerization rate α of the silica S2 according to the invention is 26% higher than the depolymerization rate of CS2, which indicates that the silica S2 has a better depolymerization tendency.
[0183] Example 4
[0184] 1104 liters of water were introduced into a 2500 liter reactor and heated to 90° C. 17.6 kg of solid sodium sulfate were introduced into the reactor under stirring. Sulfuric acid (concentration: 96 wt %) was then added until the pH of the mixture reached 4.1.
[0185] Sodium silicate solution (with SiO2 / Na2O weight ratio equal to 3.44 and density equal to 1.231 kg / L) was introduced into the reactor simultaneously with sulfuric acid (concentration: 7.7 wt %) at a flow rate of 430 l / h over a period of 25 minutes. The flow rate was adjusted so that the pH of the reaction medium was maintained at a value of 4.1.
[0186] After 25 minutes of simultaneous addition at 90° C., the introduction of acid was stopped and the pH was allowed to reach a value of 8.0. At the same time, the temperature was raised to 94° C. Further simultaneous additions were then carried out over a period of 13 minutes at a flow rate of 701 L / h of sodium silicate and of regulated sulfuric acid (concentration: 96 wt %) in order to maintain the pH of the reaction medium at a value of 8.0.
[0187] After this simultaneous addition, the reaction medium was brought to a pH of 4.5 by introducing sulfuric acid (concentration: 96 wt %). 2060 liters of precipitated silica suspension were obtained after this operation.
[0188] The precipitated silica suspension was filtered on a filter press and washed to give a precipitated silica cake having a solids content of 20.4% by weight.
[0189] The obtained silica cake was subjected to a liquefaction step by adding 1642 g of a phosphoric acid solution with a concentration of 1 mol / L to the cake in a reactor with continuous and vigorous stirring to reach a pH of 4.6.
[0190] This liquefied cake is then dried using a nozzle atomizer to provide silica S3. The properties of silica S3 are reported below.
[0191] Example 5
[0192] 15.7 L of purified water and 244 g of Na2SO4 (solid) were introduced into a 25 L stainless steel reactor. The solution was stirred and heated to 92° C. The entire reaction was carried out at this temperature. Sulfuric acid solution (concentration: 7.7 wt %) was metered into the reactor until the pH of the medium reached a value of 4.5.
[0193] Then, sodium silicate solution (SiO / Na O ratio = 3.43; SiO concentration = 19.6 wt %) and sulfuric acid (concentration: 7.7 wt %) were introduced simultaneously at a flow rate of 103 g / min over a period of 12.5 min. The flow rate of the sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 4.5.
[0194] The introduction of acid was stopped while the addition of silicate was maintained at a flow rate of 108 g / min until the pH of the reaction medium reached a value of 8.0.
[0195] At the same time, sodium silicate and sulfuric acid (concentration: 95 wt %) were metered in at a flow rate of 163 g / min over a period of 15.3 min. The sulfuric acid flow rate was adjusted so that the pH of the reaction medium was maintained at a value of 8.0.
[0196] At the end of the simultaneous addition, the pH of the reaction medium is brought to 4.8 with sulfuric acid (concentration: 95 wt %). The reaction mixture is allowed to stand for 5 minutes. The silica suspension thus obtained is filtered on a filter press and washed.
[0197] The silica cake thus obtained was subjected to a mechanical liquefaction step while adding water to a solid content of 19.7 wt.%. The pH of the resulting silica suspension was brought to 3.0 by adding sulfuric acid (concentration: 7.7 wt.%). The resulting suspension was dried by means of a nozzle spray dryer to obtain precipitated silica S4. The properties of silica S4 are reported below.
[0198] Example 6
[0199] 14.44 L of purified water and 160.8 g of Na2SO4 (solid) were introduced into a 25 L stainless steel reactor. The solution was stirred and heated to 92° C. Sulfuric acid (concentration: 7.7 wt %) was metered into the reactor until the pH of the medium reached a value of 3.9.
[0200] Sodium silicate solution (SiO2 / Na2O ratio = 3.44; SiO2 concentration = 19.62 wt%) and sulfuric acid (concentration: 7.7% wt) were introduced simultaneously at a flow rate of 103 g / min over a period of 19 min. The flow rate of sulfuric acid was adjusted so that the pH of the reaction medium was maintained at a value of 3.9. The temperature was then raised to 94°C.
[0201] The introduction of acid was stopped while the addition of silicate was maintained at a flow rate of 72 g / min until the pH of the reaction medium reached a value of 8.0.
[0202] At the same time, sodium silicate and sulfuric acid (concentration: 7.7 wt %) were metered in over a period of 16 min at a flow rate of 154 g / min. The sulfuric acid flow rate was adjusted so that the pH of the reaction medium was maintained at a value of 8.0. At the end of the simultaneous additions, the pH of the reaction medium was brought to 4.8 with sulfuric acid (concentration: 7.7 wt %). The reaction mixture was allowed to stand for 5 minutes. The silica suspension thus obtained was filtered on a filter press and washed.
[0203] The silica cake thus obtained was subjected to a mechanical liquefaction step while adding water to a solid content of 17.7%. The pH of the resulting silica suspension was brought to 3.0 by adding sulfuric acid (concentration: 7.7 wt%). The resulting suspension was dried by means of a nozzle spray dryer to obtain precipitated silica S5. The properties of silica S5 are reported below.
[0204] Example 7
[0205] Rubber compositions suitable for preparing passenger car treads were prepared according to the formulations given in Table I (the components are expressed in parts by weight per 100 parts of elastomer (phr)). Table I
[0206] Preparation of the rubber composition: The process for preparing the rubber composition is carried out in three consecutive stages. The first and second mixing stages involve thermomechanical processing at high temperatures, followed by a third mechanical processing stage at a temperature below 110° C. The latter allows the introduction of the vulcanization system.
[0207] The first and second stages were carried out with the aid of a Brabender internal mixer (cleanroom volume: 380 mL) with filling factors of 0.62 and 0.59, respectively. The initial temperature and rotor speed were fixed each time so as to achieve a mixed droplet temperature of about 140° C. to 170° C.
[0208] During a first step, elastomer, filler, plasticizer and stearic acid are mixed together; the mixing time is between 2 and 10 minutes.
[0209] After cooling the mixture (temperature below 100° C.), zinc oxide and antioxidant are incorporated into the complex during a second mixing phase. The duration of this phase is between 2 and 6 minutes.
[0210] After cooling the mixture (temperature below 100° C.), the third mixing stage allows the introduction of the vulcanization system (sulphur and accelerators). It is carried out in an open two-roll mixer preheated to 50° C. The duration of this stage is between 2 and 6 minutes.
[0211] The final rubber composition is then formed in the form of a sheet having a thickness of 2 to 3 mm.
[0212] The rheological properties of the uncured compounds were evaluated to monitor processability indicators. Once the cure properties were determined, the uncured compounds were cured at the cure optimum (T98) and the mechanical and dynamic properties were measured.
[0213] Viscosity of the uncured composition: Mooney viscosity was measured at 100° C. using a MV 2000 rheometer according to NF ISO 289. After preheating for one minute, the torque value (ML (1+4)-100° C.) was read at 4 minutes. According to DIN 53529, a strain sweep measurement from 0.3% to 50% was performed using a D-MDR 3000 rheometer at 100° C. and 1 Hz. The results are shown in Table II. Table II
[0214] The uncured composition I-1 comprising the silica S1 of the present invention shows a significant reduction in Mooney viscosity ML (1+4), storage modulus G'0.3% and Payne effect ΔG' (0.3%-50%) relative to the control composition C-1. Compared with the uncured rubber mixture containing silica CS1, the processability of the uncured rubber mixture containing the silica of the present invention is significantly improved.
[0215] Vulcanization of uncured composition: Measurements were made using an ODR MONSANTO rheometer at 160°C under 3° amplitude oscillation for 30 minutes, according to NF ISO 3417 standard. The variation of the rheological torque over time was measured. This allows the vulcanization reaction of the composition to be inferred and the following parameters to be monitored: minimum torque (minT), which reflects the torque of the uncured compound at the test temperature; maximum torque (maxT), which reflects the torque of the cured compound; Δ torque (ΔT = maxT-minT), which reflects the degree of rubber crosslinking; curing time T98 gives the time to obtain a vulcanization rate corresponding to 98% complete vulcanization (T98 is considered the optimal vulcanization); scorch time TS2 corresponds to the time required to increase the torque by 2 points above the minimum torque at the temperature considered (160°C), and it reflects the time during which the uncured composition can be processed before the vulcanization reaction begins. The results obtained are shown in Table III.
[0216] Mechanical properties of the cured composition: The Shore A hardness of the cured composition was measured according to ASTM D 2240. The value was taken after 3 seconds.
[0217] Uniaxial tensile tests were carried out on an INSTRON 5564 at a speed of 500 mm / min with H2 specimens according to NF ISO 37 standard. The moduli M100 and M300 (obtained at 100% and 300% strain, respectively) and the tensile strength are expressed in MPa; the elongation at break is expressed in %. The reinforcement index is also provided, which is defined as the ratio between the modulus obtained at 300% strain and the modulus obtained at 100% strain. The measured properties are summarized in Table III.
[0218] Dynamic properties of the cured compositions: They were measured on a viscosity analyzer (Metravib DMA+1000) according to ASTM D5992.
[0219] In the vulcanized sample (section 95mm 2 The loss factor (tan δ) and complex modulus (E * ). The sample was first subjected to a 10% prestrain and then to a ±2% sinusoidal dynamic strain amplitude. The measurements were performed at 60°C and a frequency of 10 Hz.
[0220] The results presented in Table III are the complex modulus (E * -60℃-10Hz) and loss factor (tanδ-60℃-10Hz). Table III I-1 C-1 minT(dN.m) 17.2 18.6 maxT(dN.m) 58.4 57.7 ΔT(dN.m) 41.2 39.1 TS2(min) 4.7 4.3 T98(min) 27.6 26.8 Shaw A-3s(pts) 54 56 Modulus M100(Mpa) 1.8 2.1 Modulus M300(Mpa) 8.9 8.9 Tensile strength(Mpa) 16.4 14.8 Elongation at break (%) 440 418 M300 / M100 4.9 4.2 <![CDATA[E * 10+ / -2%(MPa)]]> 4.9 5.5 tanδ10+ / -2% 0.104 0.109
[0221] At a comparable vulcanization time T98, composition I-1 comprising silica S1 of the invention shows an increase in scorch time relative to composition C-1. The increase in scorch time is advantageous because it provides increased thermal stability during the extrusion process without substantially increasing the length of the vulcanization process step. Composition I-1 also shows an increase in reinforcement index and tensile strength, resulting in an improvement in the wear resistance of the elastomeric composition.
[0222] Overall, composition I-1 with a high plasticizer loading shows an improvement in the compromise between processability and wear performance compared to composition C-1 containing silica CS1.
[0223] Example 8
[0224] Rubber compositions suitable for passenger car treads were prepared according to the formulations given in Table IV (the components are expressed in parts by weight per 100 parts of elastomer (phr)). Table IV
[0225] Preparation of the rubber composition: The process for preparing the rubber composition is carried out in two consecutive stages. A first mixing stage involves thermomechanical processing at high temperature, followed by a second mechanical processing stage at a temperature below 110° C. The latter allows the introduction of the vulcanization system.
[0226] The first stage was carried out with the aid of a Brabender internal mixer (cleanroom volume: 380 mL) with a filling factor of 0.62. The initial temperature and rotor speed were fixed so as to achieve a mixed droplet temperature of about 140° C. to 170° C.
[0227] After cooling the mixture (temperature below 100° C.), the second mixing stage allows the introduction of the vulcanization system (sulphur and accelerators). It is carried out in an open two-roll mixer preheated to 50° C. The duration of this stage is between 2 and 6 minutes.
[0228] The final rubber composition is then formed in the form of a sheet having a thickness of 2 to 3 mm.
[0229] The rheological properties of the uncured compounds were evaluated to monitor processability indicators. Once the cure properties were determined, the uncured compounds were cured at the cure optimum (T98) and the mechanical and dynamic properties were measured.
[0230] The viscosity of the uncured composition
[0231] The Mooney viscosity was measured under the same conditions as in Example 6. The strain sweep measurement from 0.9% to 50% was carried out at a temperature of 100° C. and a frequency of 1 Hz using a D-MDR 3000 rheometer according to DIN 53529. The results are shown in Table V. Table V I-2 C-2 ML(1+4)-100℃(MU) 107 116 G'0.9%-100℃(kPa) 485 566 ΔG'(0.9%-50%)-100℃(kPa) 591 757
[0232] The uncured composition I-2 comprising the silica S1 of the present invention shows a significant reduction in Mooney viscosity ML (1+4), storage modulus G'0.9% and Payne effect ΔG' (0.9%-50%) relative to the control composition C-2. The processability of the uncured rubber mixture containing the silica of the present invention is significantly improved compared to the silica CS1 having a higher pH.
[0233] The vulcanization of the uncured compositions and the mechanical properties of the cured compositions were evaluated under the same conditions as in Example 6. The results are collected in Table VI. Table VI
[0234] Composition I-2 comprising silica S1 according to the invention shows an increase in scorch time relative to control composition C-2 without slowing down the vulcanization speed. It also has an increased reinforcement index at comparable tensile strength, leading to an improvement in the wear resistance of the elastomeric composition.
[0235] Dynamic properties of the cured composition: measured on a viscosity analyzer (Metravib DMA+1000) according to ASTM D5992.
[0236] Dynamic response of compositions cured under strain sweep conditions
[0237] According to the cycle, the sample (cross section 8mm) was subjected to a temperature of 40°C and a frequency of 10 Hz. 2 , height 7 mm) were subjected to sinusoidal deformation under alternating double shear with a forward cycle range of 0.1% to 50% and a return cycle range of 50% to 0.1%.
[0238] The maximum loss factor (tan δ max ), shear storage modulus (G' 0.1% , G' 50% ) and Payne effect (G' 0.1% -G' 50% The results are shown in Table VII. Table VII I-2 C-2 <![CDATA[G' 0.1% (MPa)]]> 3.5 4.6 <![CDATA[G' 0.1% -G' 50% (MPa)]]> 2.3 3.1 <![CDATA[tanδ max ]]> 0.204 0.214
[0239] Composition I-2 exhibits a reduced Payne effect and a reduced maximum loss factor tan δmax. These two effects lead to an improvement in the energy dissipation capacity of the composition and thus to a reduction in the rolling resistance of the final tire.
[0240] Dynamic response of compositions cured under temperature sweep conditions
[0241] The specimens (cross section 8 mm2) were tested under 1% alternating double shear sinusoidal deformation and a frequency of 10 Hz in a temperature sweep from -45°C to +45°C (heating rate +5°C / min). 2 , height 7 mm). The maximum loss factor (tan δmax) was measured. The results are summarized in Table VIII. Table VIII I-2 C-2 tanδmax 0.976 0.892 <![CDATA[T max (℃)]]> -19.8 -19.3
[0242] Composition I-2 containing silica S1 shows an increase in the maximum loss factor (tan δ max ), which can be correlated to an improvement in the wet grip properties of the tire.
[0243] Overall, the use of the silica of the present invention in the preparation of rubber compositions using short mixing times (2 mixing stages in total) provides an improvement in the compromise between processability, energy dissipation, wet grip and wear performance compared to compositions containing silica with a higher pH.
Claims
1. A precipitated silica, characterized in that: -More than 140m 2 CTAB surface area S / g CTAB ; - an aggregate size distribution width Ld of at least 1.2, defined as Ld = (d84 - d16) / d50, determined by centrifugal sedimentation in a disc centrifuge; - pH less than 5.5; - A carbon content of less than 1500 ppm; and - greater than 3.5 per nm 2 The amount of silanol SiOH.
2. The precipitated silica according to claim 1, further characterized in that: It has a value equal to or greater than 0.5×10 -2 μm -1 min -1 The depolymerization rate α.
3. The precipitated silica according to claim 2, wherein the depolymerization rate α of the precipitated silica is greater than that of the precipitated silica having the same CTAB surface area S CTAB and the aggregate size distribution width Ld but the deagglomeration rate α of the precipitated silica having a higher pH is at least 15% higher.
4. The precipitated silica according to any one of claims 1 to 3, wherein The CTAB surface area S CTAB More than 160m 2 / g.
5. The precipitated silica according to claim 4, wherein The CTAB surface area S CTAB At 170m 2 / g to 400m 2 / g range.
6. The precipitated silica according to any one of claims 1 to 3, wherein The CTAB surface area S CTAB More than 180m 2 / g.
7. The precipitated silica according to claim 6, wherein The CTAB surface area S CTAB At 200m 2 / g to 350m 2 / g range.
8. The precipitated silica according to any one of claims 1 to 3, wherein The CTAB surface area S CTAB More than 200m 2 / g.
9. The precipitated silica according to claim 8, wherein The CTAB surface area S CTAB At 220m 2 / g to 350m 2 / g range.
10. The precipitated silica according to any one of claims 1 to 3, wherein The CTAB surface area S CTAB More than 230m 2 / g.
11. The precipitated silica according to claim 10, wherein The CTAB surface area S CTAB Less than 350m 2 / g.
12. The precipitated silica according to any one of claims 1 to 3, wherein The pH is less than 5.
0.
13. The precipitated silica according to claim 12, wherein The pH is less than 4.
5.
14. The precipitated silica according to any one of claims 1 to 3, wherein The CTAB surface area S CTAB At 200m 2 / g to 350m 2 / g range and the pH is less than 5.
0.
15. The precipitated silica according to any one of claims 1 to 3, wherein The CTAB surface area S CTAB At 220m 2 / g to 350m 2 / g range and the pH is less than 4.
5.
16. The precipitated silica according to any one of claims 1 to 3, wherein The carbon content is less than 10 ppm.
17. A method for preparing precipitated silica according to any one of claims 1 to 16, comprising the following steps: (i) providing a starting solution having a pH of 2.0 to 5.0, (ii) adding silicate and acid to the starting solution simultaneously such that the pH of the reaction medium is maintained in the range of 2.0 to 5.0, (iii) stopping the addition of said acid and said silicate and adding a base to the reaction medium to raise the pH of said reaction medium to a value of 7.0 to 10.0, said base being one or more than one base comprising the group consisting of silicates, (iv) adding silicate and acid simultaneously to the reaction medium such that the pH of the reaction medium is maintained in the range of 7.0 to 10.0, (v) stopping the addition of the silicate while continuing to add the acid to the reaction medium to reach a pH of the reaction medium of less than 5.5 and obtaining a first suspension of precipitated silica, and (vi) filtering the first suspension of precipitated silica to provide a filter cake; (vii) subjecting the filter cake to a liquefaction step in the presence of an inorganic acid so that the pH of the resulting precipitated silica is less than 5.5 to obtain a second suspension of precipitated silica; and (viii) optionally, drying the precipitated silica obtained after the liquefaction step.
18. The method according to claim 17, wherein: The inorganic acid used in the liquefaction step is selected from sulfuric acid, hydrochloric acid, phosphoric acid and nitric acid.
19. The method according to any one of claims 17 to 18, wherein: In step (iii) the addition of the acid is stopped while continuing to add the silicate to the reaction medium to raise the pH of the reaction medium to a value between 7.0 and 10.
0.
20. A composition comprising the precipitated silica according to any one of claims 1 to 16 and at least one elastomer.
21. A tire comprising the precipitated silica according to any one of claims 1 to 16.
Citation Information
Patent Citations
Reinforcing aluminous filler and rubber composition comprising such a filler
WO1999028376A2
Method of preparing silicas, silicas with specific pore-size and / or particle-size distribution and the use thereof, in particular for reinforcing polymers
WO2003016215A1